2017
DOI: 10.1177/1039856217706823
|View full text |Cite
|
Sign up to set email alerts
|

Inter-agency collaboration between mental health services and police in Queensland

Abstract: Queensland has developed a number of initiatives for intervention and response to incidents involving police and persons with mental illness. Future research should focus on identifying interventions that promote effective resolution of incidents involving police.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In Queensland, the Consumer Integrated Mental Health Application (CIMHA) was implemented in 2008. CIMHA contains all patient information including diagnoses, alerts and service episode information, clinical outcome measures and risk assessments and is accessible online to approximately 6,400 mental health service personnel throughout Queensland, including Court Liaison Service clinicians in watch houses and the Prison Mental Health Service (Scott & Meehan 2017). Thus, steps have already been taken to improve gaps in access to essential information for diagnosis and treatment of PSMDs.…”
Section: Discussionmentioning
confidence: 99%
“…In Queensland, the Consumer Integrated Mental Health Application (CIMHA) was implemented in 2008. CIMHA contains all patient information including diagnoses, alerts and service episode information, clinical outcome measures and risk assessments and is accessible online to approximately 6,400 mental health service personnel throughout Queensland, including Court Liaison Service clinicians in watch houses and the Prison Mental Health Service (Scott & Meehan 2017). Thus, steps have already been taken to improve gaps in access to essential information for diagnosis and treatment of PSMDs.…”
Section: Discussionmentioning
confidence: 99%
“…Most jurisdictions across Australia have formalised interagency collaborations through a Memorandum of Understanding (MOU), which is a written agreement regarding the sharing of information and safe handling of PWMI in crisis between police and health staff (Clifford, 2010). In some Australian jurisdictions, important information can be promptly conveyed to a police officer attending a PWMI in crisis via telecommunication from a mental health clinician (Scott & Meehan, 2017). Research from the UK has shown how knowledge sharing between first responders to PWMI in crisis can better inform an officer's judgements in making more therapeutic decisions when interaction occurs, such as not arresting, restraining and detaining the PWMI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…International research determines that CIT schemes and other interagency response initiatives provide positive accounts of equitable treatment of PWMI in crisis (see Evangelista et al, 2016; Furness et al, 2016; Hanafi et al, 2008; Herrington & Pope, 2013; Morgan & Paterson, 2017; Scott & Meehan, 2017). Whilst Australian research examining these initiatives is still in need of systematic enquiry, studies by Clifford (2021) and Evangelista et al (2016) suggest that collaborative approaches between police and mental health professionals are pivotal in therapeutically de-escalating PWMI during the crisis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A key component of the training is that PWMI and their carers present real-life examples of policing of PWMI in crisis to police to expose officers to a humanising perspective of police treatment from those with lived experiences of mental illness (NSW Police Force 2020). Across Australia and internationally, early reports of CIT and other interagency schemes provide positive accounts of police discretion control and enhanced equitable treatment of PWMI when encountering the police (Evangelista et al 2016;Furness et al 2016;Hanafi et al 2008;Herrington and Pope 2013;Morgan and Paterson 2017;Scott and Meehan 2017).…”
Section: Introductionmentioning
confidence: 99%